The Effect of Work Compensation and Leadership Style on Employee Job Satisfaction with Organizational Citizenship Behavior (OCB) as a Mediating Variable at PT. Paguntaka Cahaya Nusantara - Apriawan, Andry; Lahindah, Laura (International Journal Labs, 2025)
In the globalization era, competition demands every company to implement effective Human Resource Management (HRM) practices, where employee job satisfaction has become a key factor affecting organizational performance. This study aims to analyze the effect of work compensation and leadership style on employee job satisfaction with Organizational Citizenship Behavior (OCB) as a mediating variable at PT. Paguntaka Cahaya Nusantara. This research uses quantitative associative approach with 110 permanent employees as respondents selected through purposive sampling technique. Data collection was conducted using questionnaires with Likert scale 1-5, and data analysis used multiple linear regression with SPSS. The results show that work compensation and leadership style have significant positive effects on job satisfaction both partially and simultaneously. OCB significantly mediates the relationship between work compensation and job satisfaction, but does not significantly mediate the relationship between leadership style and job satisfaction. The coefficient of determination shows that 68.9% of job satisfaction variation can be explained by work compensation and leadership style variables. This research contributes to human resource management theory and provides practical recommendations for companies to improve compensation policies and leadership approaches to enhance employee job satisfaction.